Pengaruh Kompetensi Asisten Laboratorium, Fasilitas Praktik, Jobsheet Praktik dan Pemahaman Teori terhadap Kompetensi Mahasiswa Pendidikan Vokasional - Reza Prasetya Putera; Irwanto Irwanto; Bagus Dwi Cahyono (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Education is an important thing at this time, especially in college. One form of education is practical activities carried out to improve student experience and understanding. Things that affect student competence are the competence of laboratory assistants, practical facilities, practical worksheets and theoretical understanding. This study was conducted to determine the magnitude of the influence of the competence of laboratory assistant practical facilities, practical jobsheets and theoretical understanding on the competence of students of Electrical Engineering Vocational Education, University of Sultan Ageng Tirtayasa. This study is an ex-post facto research using quantitative research methods whose data were obtained using questionnaires and tests distributed to students of Electrical Engineering Vocational Education at Sultan Ageng Tirtayasa University who did practicum and then processed using the SPSS 25.0 application with simple linear regression analysis techniques and also regression double. The results of the study showed that there was a significant effect of the laboratory assistant competency variable, while the practical facilities variable, practical worksheet and theoretical understanding did not have a significant influence on the student competency variable. Keywords: Practice, Laboratory Assistant, Facilities, Jobsheet, Theory Understanding